The Effect of Competency, Work Life Balance and the Use of Information Technology on Employee Performance at the Best Western Kamala Jimbaran Hotel, Bali - I Gusti Ngurah Putu Surya Pratama Putra; Ketut Sudarmini; Bayu Pasupati (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to understand the extent to which each independent variable contributes to employee performance at the Best Western Kamala Jimbaran Hotel. This research uses a quantitative approach, analyzing multiple linear regression with 46 participants. Data were obtained from questionnaires that were tested for reliability and validity, as well as classical assumption tests, including multicollinearity, heteroscedasticity, and normality. Each independent variable contributed significantly and positively to employee performance. High employee competency, a balance between work and personal life, and optimal use of information technology will improve employee performance. Therefore, it is recommended that hotel managers develop competencies, support work-life equality, and maximize the use of information technology to improve performance.